2017
DOI: 10.18844/gjpr.v7i1.2433
|View full text |Cite
|
Sign up to set email alerts
|

Negative and positive perfectionism as predictors of procrastination in female high school students in Tehran, Iran

Abstract: Research has shown a relationship between procrastination and perfectionism, i.e. perfectionists generally tend to procrastinate. Therefore, the present study evaluated negative and positive perfectionism as predictors of procrastination in female high school students. This correlational study was conducted in 2015-16 academic year. The statistical population comprised all high school sophomores and juniors in Tehran, Iran. The research sample consisted of 300 female students. During the field data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Moreover, mentoring and student-focused intervention were more used in Keren secondary schools in managing students' discipline. Furthermore, this study revealed that students received more advice concerning educational matters than discipline issues (Mikaeli Manee & Aria, 2018;Shirzad, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, mentoring and student-focused intervention were more used in Keren secondary schools in managing students' discipline. Furthermore, this study revealed that students received more advice concerning educational matters than discipline issues (Mikaeli Manee & Aria, 2018;Shirzad, 2017).…”
Section: Discussionmentioning
confidence: 77%